2002
DOI: 10.1590/s1517-74912002000400004
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of the optical density of packable composites: comparison between direct and indirect digital systems

Abstract: The aim of this study was to measure the optical density of four packable composite resins with widths of 1, 2, 3 and 4 mm, by means of Digora (direct) and DentScan DentView (indirect) digital imaging systems, in order to compare both methods. Twenty acrylic plates, with the proposed thicknesses, were used, each one containing a sample of each resin. Each acrylic plate was radiographed three times, under a standardized technique. For the Digora system, an optical plate was used under each resin sample, and, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
0
4
0
2
Order By: Relevance
“…All endodontic filling materials had higher radiopacity values on digital images regardless of their composition. Similarly, comparing the optical density values of composite resins using Digora SPP images and digitized films, Graziottin et al (2002) reported that Digora images had higher and more homogenous radiopacity values. This difference may be attributed to the different image acquisition technologies of digital image receptors.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…All endodontic filling materials had higher radiopacity values on digital images regardless of their composition. Similarly, comparing the optical density values of composite resins using Digora SPP images and digitized films, Graziottin et al (2002) reported that Digora images had higher and more homogenous radiopacity values. This difference may be attributed to the different image acquisition technologies of digital image receptors.…”
Section: Discussionmentioning
confidence: 96%
“…2008). Additionally, indirectly digitized radiographs tend to have higher variation of the grey level, as read‐out depends on the specific characteristics of the scanner (Graziottin et al. 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Digital cameras require adjusting of the radiographic and zooming distance 28 of the camera; this can cause distortion of the image, depending on the values chosen for the photographic parameters, such as diaphragm aperture, exposition time and sensor sensibility. 29 In addition, radiographic images obtained by the indirect technique tend to exhibit a higher gray level variation, because the variability of grayscale values depends on the specific characteristics of the scanner 30 or photographic camera used.…”
Section: Discussionmentioning
confidence: 99%
“…No presente estudo foram utilizadas cartelas tipo blíster de fundo reto para a confecção dos corpos de prova, a fim de que a espessura dos mesmos fosse padronizada para os três materiais, evitando assim que a espessura interferisse nos resultados. A espessura utilizada foi de 2,0 mm, considerando que à medida que a espessura do material aumenta, há uma maior produção de valores de densidade óptica (GRAZIOTTIN et al, 2001;GRAZIOTTIN et al, 2002…”
Section: Discussionunclassified